Hepatocyte nuclear factor 4-α is necessary for high fat diet-induced pancreatic β-cell mass expansion and metabolic compensations - de Ramos, Francieli Caroline; Barth, Robson; Santos, Marcos Rizzon; Almeida, Milena dos Santos; Ferreira, Sandra Mara; Rafacho, Alex; Boschero, Antônio Carlos; Santos, Gustavo Jorge dos (Frontiers in Endocrinology, 2024)
AimsThis study investigates the role of Hepatocyte Nuclear Factor 4α (HNF4α) in the adaptation of pancreatic β-cells to an HFD-induced obesogenic environment, focusing on β cell mass expansion and metabolic adaptations.Main methodsWe utilized an HNF4α knockout (KO) mouse model, with CRE-recombinase enzyme activation confirmed through tamoxifen administration. KO and Control (CTL) mice were fed an HFD for 20 weeks. We monitored body weight, food intake, glucose tolerance, insulin sensitivity, and insulinemia. Also, to assess structural and metabolic changes, histological analyses of pancreatic islets and liver tissue were conducted.Key findingsKO mice displayed lower fasting blood glucose levels compared to CTL mice after tamoxifen administration, indicating impaired glucose-regulated insulin secretion. HFD-fed KO mice consumed less food but exhibited greater weight gain and perigonadal fat accumulation, reflecting higher energy efficiency. Histological analysis revealed more pronounced liver steatosis and fibrosis in KO mice on HFD. Glucose intolerance and insulin resistance were exacerbated in KO mice, highlighting their inability to adapt to increased metabolic demand. Structural analysis showed that KO mice failed to exhibit HFD-induced β cell mass expansion, resulting in reduced islet diameter and number, confirming the critical role of HNF4α in β cell adaptation.SignificanceThis study demonstrates that HNF4α is essential for the proper metabolic and structural adaptation of pancreatic β-cells in response to an obesogenic environment. The lack of HNF4α impairs β cell functionality, leading to increased susceptibility to glucose intolerance and insulin resistance. These findings underscore the importance of HNF4α in maintaining glucose homeostasis and highlight its potential as a therapeutic target for diabetes management in obesity.